2008
DOI: 10.1016/j.bbr.2007.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ultrasonic vocalizations in vasopressin 1b knockout mice

Abstract: The neuropeptides oxytocin and vasopressin have been implicated in rodent social and affiliative behaviors, including social bonding, parental care, social recognition, social memory, vocalizations, territoriality, and aggression, as well as components of human social behaviors and the etiology of autism. Previous investigations of mice with various manipulations of the oxytocin and vasopressin systems reported unusual levels of ultrasonic vocalizations in social settings. We employed a vasopressin 1b receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 59 publications
9
119
0
Order By: Relevance
“…For example, AVT administration induces vocalizations in the plainfin midshipman fish [19] and in white-crowned sparrows [32] while ultrasonic vocalizations are impaired in AVP 1b knockout mice [46]. AVP administration even affects social communication [53] and speech [62] in humans.…”
Section: Discussionmentioning
confidence: 98%
“…For example, AVT administration induces vocalizations in the plainfin midshipman fish [19] and in white-crowned sparrows [32] while ultrasonic vocalizations are impaired in AVP 1b knockout mice [46]. AVP administration even affects social communication [53] and speech [62] in humans.…”
Section: Discussionmentioning
confidence: 98%
“…The baseline rate of isolation-induced vocalizations in pups may serve as an early biomarker of communicative function in mice, and a large number of mouse lines with mutations in autism candidate genes show changes in baseline vocalization rates (3). Although both WT and TSC2 +/− pups born to WT dams expressed no difference in baseline rates compared with each other or with C57BL/ 6J mice in other studies (11,13), pups born to TSC2 +/− dams showed baseline rates roughly 3-fold that of their WT-dam counterparts. This dramatic increase in overall vocalizations may reflect a particularly heightened anxiety state, as vocalization rates are known to be susceptible to anxiolytic drugs, whereas anxiogenics increase call number and amplitude (14).…”
Section: Tsc2 Dam Haploinsufficiency Alters Baseline Vocalization Ratmentioning
confidence: 93%
“…Although baseline vocalizations provide insight into the pups' immediate response to isolation, maternal potentiation highlights the influence of mother-pup interaction on vocalization as social communication. Baseline vocalizations have typically been interpreted as distress calls, susceptible to changes in temperature and other environmental cues, whereas maternal potentiation is robust in rats and mice, independent of temperature and specific to reunion with a familiar parent (13). During the reunion period, the pup may associate maternal retrieval as a reward for cries, and thus on a subsequent isolation, the pup cries out even more vehemently.…”
Section: Changes In Maternal Potentiation Are Dependent On Genotype Ofmentioning
confidence: 99%
“…Juveniles were tested for reciprocal social play and open field exploratory locomotion. Adults were tested for social approach in an automated three-chambered sociability apparatus, elevated plus maze and light↔dark anxiety-related behaviors, general health and home cage measures including nesting, neurological reflexes, open field locomotion, rotarod coordination and balance, forepaw reaching for vision, acoustic startle threshold for hearing, prepulse inhibition of acoustic startle for sensorimotor gating, hot plate and tail flick for pain sensitivity, contextual and cued fear conditioned learning and memory, and Morris water maze spatial learning and memory acquisition and reversal, as previously described (Crawley and Goodwin, 1980;Bailey et al, 2007;Crawley, 2007;Crawley et al, 2007;Moy et al, 2007;Yang et al, 2007;McFarlane et al, 2008;Scattoni et al, 2008) and described in detail in the Supplementary Methods. Figure 2A-D documents no significant differences between male genotypes for A) follow (F 2,28 = 0.157, NS), B) nose-to-nose sniff (F 2,28 = 0.087, NS), C) push-crawl-touch (F 2,28 = 2.031, NS) or D) social groom (F 2,28 = 0.337, NS).…”
Section: Behavioral Testsmentioning
confidence: 99%